On-the-Job Learning: How Peers and Experience Drive Productivity Among Teachers - Romaine A. Campbell; Seth Gershenson; Constance A. Lindsay; Nicholas W. Papageorge; Jessica H. Rendon (Institute of Labor Economics (IZA), 2024)
Workers learn on the job from both repetition and peers. Less understood is how specific types of experience and peer characteristics affect on-the-job learning. This likely differs by context (e.g., occupation, tasks, or roles). Absent such knowledge, it is unclear how to optimally assign workers to tasks and peers. We examine on-the-job learning among elementary school teachers. We focus on white teachers' productivity teaching Black students. We examine specific types of experience and specific types of peers that could lead to rapid productivity gains for white teachers: experience teaching Black students and having Black colleagues. Both lead to significant productivity gains over and above those associated with total teaching experience and access to generally productive peers. This is due to learning, as peer effects are persistent and driven by more effective Black peers. These findings offer insights to improving Black students' educational outcomes when facing a disproportionately white teaching force. More generally, they underscore the importance of understanding whether and how nuanced types of experiences and peers enter the production function and drive on-the-job human capital accumulation.
Keywords: I2; J24; D2; 330; peer effects; knowledge spillovers; teacher effectiveness; teacher diversity; achievement gaps; education production function; learning-by-doing; human capital